Linear Regression Analysis on predicting the level of damage and changes in Amal Baru Beach Tarakan City Indonesia - Muhammad Djaya Bakri; Edy Utomo; Daud Nawir (SINERGI, 2023)
Amal Baru Beach is one of the tourist beaches on Tarakan Island; where for the last ten years, this beach has experienced a change in the function of its coastal area, which has become a seaweed cultivation area. These cause changes to the coastline and the area of the indicative area on the beach, besides being influenced by the characteristics of the waves that occur. Based on this, in this study, a study was conducted to determine the level of change in the coastline by applying the spatial analysis method of satellite imagery. The shoreline change rate is determined based on the LRR (Linear Regression Rate) method, which is applied to 25 sections within three years of changing satellite image samples. Based on the study conducted, it was found that there was severe damage to the coastline of 66.67% and 33.33% experienced moderate damage, with a rate of change of the coastline for a severe level of 2-5 m/year. In addition, the coastal area has also experienced a reduction in area, namely at a rate of reduction per year of 0,297 ha/year, with 72% damage caused by abrasion events. Based on the level of damage that occurred, it is necessary to protect the beach by constructing coastal protection structures. The recommendations for the types of coastal buildings given are Groynes and Detached Breakwater, which will be studied in further research.